Scientific Opinion of the Scientific Panel on Plant Protection Products and their Residues (PPR Panel) on the genotoxic potential of triazine amine (metabolite common to several sulfonylurea active substances). (9th March 2020) - ,; Hernandez‐Jerez, Antonio F; Adriaanse, Paulien; Aldrich, Annette; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Gimsing, Anne Louise; Marinovich, Marina; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; et al.
Abstract: The Panel received a mandate from the European Commission to assess the genotoxic potential of triazine amine based on available information submitted by the applicants. Available information includes experimental genotoxicity data on triazine amine, Quantitative Structure–Activity Relationship (QSAR) analysis and read across with structurally similar compounds. Based on the overall weight of evidence, the Panel, in agreement with the cross‐cutting Working Group Genotoxicity, concluded that there is no concern for the potential of triazine amine to induce gene mutations and clastogenicity; however, the potential to induce aneugenicity was not adequately investigated. For a conclusion, an in vitro micronucleus assay performed with triazine amine would be needed.